Hubungan Antara Motivasi Kerja Dan Disiplin Kerja Dengan Prestasi Kerja Guru SMK Sejahtera Jakarta - Pikriana, Pikriana; Aprilianto, Andika; Warti'ah, Warti'ah (Program Studi Pendidikan Agama Islam, 2023)
This research aims to analyse the relationship between work motivation and discipline and teachers' work performance at SMK Sejahtera Jakarta. Specifically, this research identifies factors that influence teacher work motivation and work discipline, measures the level of work motivation, work discipline and teacher work performance, and analyses the relationship between these three variables. The research method used was a survey method with a population of 38 teachers and a sample of 35 teachers taken randomly. The research instrument uses a questionnaire with a Likert scale. Data were analysed using descriptive and inferential statistics and correlation and regression tests. The research results show a significant positive relationship between work motivation and teacher work performance, work discipline and teacher work performance, and work motivation and work discipline together with teacher work performance. Work motivation contributes 58% to teacher work performance, while work discipline contributes 42%. Work motivation and discipline contribute 66% to teacher work performance. This research contributes to the development of human resource management science in the educational context, as well as providing practical insight for education stakeholders in an effort to improve teacher work performance through increasing work motivation and work discipline.